Regulatory Convergence of Trade Secret Licensing Agreements in Indonesia Through a Comparative Study of Taiwan and the United States - Axara Alejendra Anjani; Rianda Dirkareshza (Green Publisher Indonesia, 2025)
The protection of trade secrets plays a vital role in safeguarding a nation’s competitive edge, particularly amid globalization and economic integration. Indonesia has enacted a legal basis through Law No. 30 of 2000; however, its practical enforcement still encounters obstacles related to legal certainty, law enforcement, and procedural consistency. This research examines the protection of trade secrets in Indonesia by comparing it with Taiwan and the United States, while also exploring the possible adoption of best practices to enhance national competitiveness. The study employs a normative juridical method combined with a comparative approach and regulatory analysis, relying on literature reviews of legislation, international instruments, and relevant scholarly works. The findings suggest that incorporating best practices—such as preliminary injunctions, whistleblower immunity, stricter sanctions, and improved inter-agency collaboration—could significantly strengthen trade secret protection in Indonesia. Recommendations are directed toward the Directorate General of Intellectual Property (DGIP), the Ministry of Trade, and the Supreme Court to develop technical guidelines, establish a dedicated task force, and provide information security training for businesses, thereby aligning Indonesia’s trade secret protection framework with global standards.